2011
DOI: 10.1016/j.it.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signals regulate hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) are the progenitors of all blood and immune cells; yet their role in immunity is not well understood. Most prior studies have focused on the ability of committed lymphoid and myeloid precursors to replenish immune cells during infection. Recent studies, however, have indicated that HSCs also proliferate in response to systemic infection to replenish effector immune cells. Inflammatory signaling molecules including interferons, tumor necrosis factor-α, and Toll-like receptors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
314
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(323 citation statements)
references
References 86 publications
8
314
0
1
Order By: Relevance
“…9,[54][55][56][57][58] It is worthwhile mentioning that Sca-1 becomes aberrantly expressed and some of the HSCs in this case are in fact myeloid progenitors, when IFNs are upregulated as in the current transgenic mouse. 59,60 Taking these previous reports into account, there could have been an increase in the frequency of myeloid progenitors in the BM of T-bet tg mice, which is also in line with the result of the CFC assay. Notably, we found that monocytic differentiation became nonintrinsically impaired at the HPC level in T-bet tg/tg BM.…”
Section: Blood 8 January 2015 X Volume 125 Number 2 Aberrant T Cellsupporting
confidence: 77%
“…9,[54][55][56][57][58] It is worthwhile mentioning that Sca-1 becomes aberrantly expressed and some of the HSCs in this case are in fact myeloid progenitors, when IFNs are upregulated as in the current transgenic mouse. 59,60 Taking these previous reports into account, there could have been an increase in the frequency of myeloid progenitors in the BM of T-bet tg mice, which is also in line with the result of the CFC assay. Notably, we found that monocytic differentiation became nonintrinsically impaired at the HPC level in T-bet tg/tg BM.…”
Section: Blood 8 January 2015 X Volume 125 Number 2 Aberrant T Cellsupporting
confidence: 77%
“…The exact molecular factors and cellular mechanisms governing the quiescence and activation of dormant CSCs have been intensely investigated but remain unclear, highlighting the requirement for additional research in this area. Because inflammation has been functionally related to cancer evolution and because inflammatory signals have been shown to regulate the quiescence/activation of cancer and normal SCs [8,10,47,54,55] but not much is known concerning the circuitries connecting inflammation to melanoma development, we examined the effect of TNF, which is one of the major mediators of cancerrelated inflammatory responses [9], on melanoma cell quiescence and melanoma development in 3D tumor-like sphere and in vivo-like reconstructed skin models. Using an inducible H2B-GFP system to trace the cell divisional history in vitro, we identified quiescent/slow-cycling GFP high label-retaining CSCs in melanoma cell lines and showed that transient and chronic TNF suppresses melanoma SC differentiation while enriching for a GFP high melanosphere-initiating CSC subpopulation many generations after TNF withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the hematopoietic system, TNF was shown to have a stimulatory growth effect on hematopoietic stem cells (HSCs) but to negatively regulate the growth of their more mature progenitors in vitro [71]. In contrast, recent findings revealed that TNF suppresses cycling HSCs and their longterm repopulating activity in vivo [72] and in vitro [73], indicating that although the TNF pathway is a critical regulator of HSC maintenance and function (reviewed in [47]), the stimulatory and/or repressive effect of TNF will depend on cell types, the responding compartment and the cell status within each compartment. Little is known concerning the effect of TNF on the melanoma SC compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During biological contingencies -chemotherapy, infections and transplantation procedures-, the replenishment of the innate immune system from hematopoietic stem/progenitor cells appears to be critical. Interestingly, these seminal cells can proliferate in response to stress conditions and systemic infection by using mechanisms that apparently involve interferons and tumor necrosis factors, among others (Baldridge et al, 2011). Moreover, they are capable of self/non-self discrimination through Toll-like receptors (TLR), which recognize microbial components.…”
Section: The Early Steps In the Lymphoid Developmentmentioning
confidence: 99%